2016
DOI: 10.1002/2015gc006182
|View full text |Cite
|
Sign up to set email alerts
|

Stable and clumped isotopes in shell carbonates of land snails Cathaica sp. and Bradybaena sp. in north China and implications for ecophysiological characteristics and paleoclimate studies

Abstract: Knowledge of ecophysiological characteristics of different land snail species is crucial for defining climatic significance of snail faunal assemblages. However, little work has been done in this aspect, hindering our obtaining unambiguous paleoclimatic information using these proxy indicators. Here we document for the first time the different ecophysiological characteristics of Cathaica sp. and Bradybaena sp. land snails using the stable isotopes and clumped isotope (Δ47) of the shell carbonates. The Δ47‐deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 42 publications
3
32
3
Order By: Relevance
“…Cathaica live in groups on the trees, and they crouch on the trunk or branches to ingest food (Yang & Ren, 2012). In addition, our previous studies showed that the clumped isotope temperatures of Cathaica were 3-5°C higher than those of Bradybaena at the same study sites (Wang et al, 2016;Zhai et al, 2019). This is consistent with Cathaica's tolerance to relatively high temperature and may also reveal that the two genera have different ecophysiological habits.…”
Section: Journal Of Geophysical Research: Biogeosciencessupporting
confidence: 80%
See 2 more Smart Citations
“…Cathaica live in groups on the trees, and they crouch on the trunk or branches to ingest food (Yang & Ren, 2012). In addition, our previous studies showed that the clumped isotope temperatures of Cathaica were 3-5°C higher than those of Bradybaena at the same study sites (Wang et al, 2016;Zhai et al, 2019). This is consistent with Cathaica's tolerance to relatively high temperature and may also reveal that the two genera have different ecophysiological habits.…”
Section: Journal Of Geophysical Research: Biogeosciencessupporting
confidence: 80%
“…The lifestyle and habits of the Bradybaena genus have been extensively studied through field observations and culturing experiments, and our previous study has thoroughly summarized the findings in this respect (Wang et al, ). We thus briefly introduce the ecophysiological habits of the land snails.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The need to resort to such an exotic interpretation argues that clumped-isotope systematics, unquestionably a desirable and promising new tool, is still a technique in developmental stages, and its advantages and limitations have yet to be established. Note also that the clumped-isotope thermometer routinely yields elevated temperatures, even for "pristine" modern shells (Bergmann et al, 2018, their figure 5;Zaarur et al, 2011;Wang et al, 2016). At this stage, the meaning of the "temperature" estimates by this technique is still open to debate, as is the resistance of this isotope system to solid-state atomic-scale reordering down to low diagenetic temperatures, the stage at which newly deposited shells that initially harbor many impurities and dislocations are particularly vulnerable (Veizer and Prokoph, 2015).…”
Section: Alternate Scenario To the Hot Ocean Scenariomentioning
confidence: 99%
“…Over the last several decades, stable isotope signatures of the snail shell have been widely used for environmental and palaeoclimatic studies (Yapp, 1979;Magaritz et al, 1981;Heller, 1980, 1983;Lécolle 1985;Goodfriend 1988Goodfriend , 1992Goodfriend , 1999Bonadonna and Leone, 1995;Leng et al, 1998;Goodfriend and Ellis, 2000;Leone et al, 2000Leone et al, , 2002Zanchetta et al, 2005Zanchetta et al, , 2017Balakrishnan et al, 2005a;Colonese et al, 2007Colonese et al, , 2014Li et al, 2007;Liu et al, 2007;Yanes et al, 2008Yanes et al, , 2009Yanes et al, , 2011Yanes et al, , 2012Yanes et al, , 2013Yanes et al, , 2014Yanes et al, , 2017Yanes et al, , 2018aKehrwald et al, 2010;Huang et al, 2012;Yanes 2015;Prendergast et al, 2015Prendergast et al, , 2016Prendergast et al, , 2017Wang et al, 2016;Bao et al, 2018).…”
Section: Introductionmentioning
confidence: 99%